AN INVESTIGATION ON YIELD AND COMPOSITION OF MILK, CALVING INTERVAL AND REPEATABILITIES IN RIVERINE BUFFALOES OF ANATOLIA - S. Koçak; M. Tekerli; K. Çelikelo lu; M. Erdoan; Z. Bozkurt; Ö. Hacan (Journal of Animal and Plant Sciences, 2019)
The objective of this study was to determine the effects of some environmental factors on the lactation milk yield, milk composition (fat, protein and lactose), lactation length and calving interval of the Anatolian buffalo and to estimate of repeatability for the investigated characteristics. Data were obtained from 1749 Anatolian buffaloes maintained at 134 farm operations between 2012 and 2016 in Afyonkarahisar province of Turkey. The record numbers used for analyses of lactation milk yield, milk content and calving interval were 4379, 1123 and 2298 respectively. The overall means, with respect to the Anatolian buffaloes, the lactation milk yield and lactation length were determined as 1087.49 ± 5.91 kg and 245.43 ± 0.90 days respectively. Also, the fat, protein and lactose yield of milk were 79.54 ± 1.15, 44.87 ± 0.53 and 63.70 ± 0.79 kg respectively. The overall mean of the calving interval was 450.35 ± 2.98 days. The effects of the farm operation, calving year, season and age on these characteristics were found to be significant (p<0.01, p<0.001). The repeatability estimates of lactation milk yield, lactation length, as well as the fat, protein and lactose yields of the milk were 0.389, 0.196, 0.399, 0.429 and 0.417 respectively. They were all statistically significant (p<0.001). It was concluded that the factors affecting milk production and reproduction must be considered in a selection program. Also, after corrections according to factors deemed significant in terms of milk yield and composition, buffaloes could be selected based on the first lactation milk yield in early ages.
Keywords: Buffaloes; milk; milk composition; repeatability